Synthesis of hydroxyapatite nanoparticles and its effect on Raphanus sativus seedlings - Flores-Hernández, Eduardo Arón; Lira Saldivar, Ricardo Hugo; Ruiz Torres, Norma Angélica; García López, Josué Israel; Moreno Reséndez, Alejandro; Rodríguez Dimas, Norma; Preciado Rangel, Pablo; Mendoza-Retana, Saraí Shesareli (Ecosistemas y Recursos Agropecuarios, 2021)
The potential of nanofertilizers to increase crop yields has recently been reported. Hydroxyapatite nanoparticles (nHAp) are applied as fertilizers to plants due to their high content of P and Ca (Ca10(PO4)6(OH)2), but there is little information in this regard. The objective of the work was to produce synthetic nHAp, characterize it and evaluate its effect as a nutrient in the development of seedlings of radish (Raphanus sativus) variety Champion. The synthesis of nHAp was carried out using an aqueous solution of calcium hydroxide [Ca(OH)2] and orthophosphoric acid (H3PO4). To analyze its biological effect, a bioassay was established with seven treatments on radish seeds with the following concentrations: control (distilled water, T1); 25 (T2); 50 (T3); 100 (T4); 200 (T5); 500 (T6) and 1000 mg L-1 (T7); the seedlings developed up to seven days after sowing. The results show that a concentration of 1 000 mg L-1 reduced germination by 14.4% compared to the control treatment (0 mL-1). While the vigor of the seedlings was reduced 11.2% with 500 mg L-1. The plumule and radicle did not show significant differences by the treatments with respect to the control, however, a statistical difference was observed with the doses of 25 and 200 mg L-1, when inhibiting and promoting the growth of the seedlings, respectively. High concentrations of nHAp were found to have adverse effects on seeds. Finally, then HAp stimulated biomass production.